Occurrence of Cryptosporidium oocysts in Wrinkled Hornbill and other birds in the Kuala Lumpur National Zoo - Rohela, M.; Lim, Y.A.; Jamaiah, I.; Khadijah, P.Y.; Laang, S.T.; Nazri, M.H.; Nurulhuda, Z. (2005)
The occurrence of a coccidian parasite, Cryptosporidium, among birds in the Kuala Lumpur National Zoo was investigated in this study. A hundred bird fecal samples were taken from various locations of the zoo. Fecal smears prepared using direct smear and formalin ethyl acetate concentration technique were stained with modified Ziehl-Neelsen stain. Samples positive for Cryptosporidium with Ziehl-Neelsen stain were later confirmed using the immunofluorescence technique and viewed under the epifluorescence microscope. Six species of bird feces were confirmed positive with Cryptosporidium oocysts. They included Wrinkled Hornbill (Aceros corrugatus), Great Argus Pheasant (Argusianus argus), Black Swan (Cygnus atratus), Swan Goose (Anser cygnoides), Marabou Stork (Leptoptilos crumeniferus), and Moluccan Cockatoo (Cacatua moluccencis). These birds were located in the aviary and lake, with the Moluccan Cockatoo routinely used as a show bird. Results obtained in this study indicated that animal sanctuaries like zoos and bird parks are important sources of Cryptosporidium infection to humans, especially children and other animals.